Rapid syphilis tests in pregnant women by primary care nurses - Bruna Britto Pereira; Cristiano Pinto dos Santos; Giovana Calcagno Gomes (Universidade Federal de Santa Maria, 2020)
Objective: to find out how primary care nurses perform rapid tests for syphilis in pregnant women. Method: this is a qualitative research conducted in a municipality in southern Brazil. Data were collected in 2018 by semi-structured interviews and submitted to Content Analysis. Results: thee nurses reported that the disease can be asymptomatic, but it has three stages. The symptoms mentioned were a vaginal wound that disappears and after that spots appear on the body. The disease can cause malformation in the newborn. The disease was unknown. When they noticed positive cases, they immediately began treatment of the pregnant woman. They emphasized the non-adherence of partners to treatment. Conclusion: the nurse's important role in prenatal and rapid syphilis testing is highlighted. Continuing education actions are needed to improve the disease indicators in the country.